Advances in the treatment of cognitive impairment in Parkinson's disease. Issue 11 (22nd August 2015) - Goldman, Jennifer G.; Weintraub, Daniel
ABSTRACT: Cognitive impairment in Parkinson's disease (PD) is a frequent complication, with significant interindividual variability in clinical symptoms, severity, timing, and neural substrates. Recent studies have focused not only on understanding PD dementia, but also mild cognitive impairment in PD, which may represent a prodromal stage for dementia. In recent years, there have been important advances regarding clinical characterizations, definitions, associated biomarkers, and risk factors for both mild cognitive impairment in PD and PD dementia. However, there is a paucity of effective therapies for cognitive impairment in PD, whether for mild symptoms or for moderate to severe dementia. At present, only rivastigmine is U.S. Food and Drug Administration approved for PD dementia, an indication received nearly a decade ago. Given the frequency of PD cognitive impairment and its substantial impact on both patients and families, the lack of available and effective treatments represents a striking gap in the field, especially when compared to the large number of available therapies for PD motor symptoms and complications. Improved symptomatic therapies, as well as potential disease‐modifying agents, for PD cognitive impairment are needed. Most therapeutic trials for PD dementia and mild cognitive impairment in PD have focused on drugs developed for and tested in Alzheimer's disease, such as cholinesterase inhibitors and the N‐methyl‐D‐aspartate receptor antagonist, memantine, though recent and ongoing trials examine the effects of pharmacological agents affecting other neurotransmitters, as well as nonpharmacological therapies, including mental and physical exercise and neurostimulation. This review summarizes the design and outcomes of trials for PD cognitive impairment published since 2013 and highlights future therapeutic research opportunities and challenges. © 2015 International Parkinson and Movement Disorder Society